(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the 1920s, theatrical art in Uzbekistan entered a period of development. People gradually grew fond of this cultural sphere. The role and status of women in this field also increased. Many women in the region began to appear on cinema and theater stages. This article discusses several women who were active in the cultural sphere, particularly Lutfikhanim Sarimsakova and Halima Nosirova. Additionally, the article discusses the policy in the cultural sphere of the Uzbekistan SSR and its shortcomings.